Does economic diplomacy influence international trade? Evidence from Tanzania - Mgeni Msafiri; Vincent Leyaro (The University of Nottingham, Centre for Research in Economic Development and International Trade (CREDIT), 2024)
Diplomatic relations have potential to enhance international trade by minimizing potential risks that firms encounter in their foreign operations, especially for developing countries. This has been a driving force for government intervention in international trade and investment through economic diplomacy. Using bilateral trade data for the period 1997 - 2019, this study examines the impact of economic diplomacy measured by the presence of embassies in Tanzania and in importer countries on Tanzanian exports and imports. The study uses augmented Pseudo Poisson Maximum Likelihood estimation to account for large proportion of zero trade flows, and a lagged trade variable to correct for the potential reverse causality of opening diplomatic representations. Results show that, on average, Tanzania exports more to countries that host Tanzanian embassies, and imports more from countries that have embassies in Tanzania. Results underscore the effective role of economic diplomacy in reducing trade barriers and foster international trade; implying that as a country Tanzania needs to enhance and strengthen its economic diplomacy with her trading partners.
Keywords: F51; F14; O55; 330; economic diplomacy; international trade; Tanzania